2015
DOI: 10.3389/fpls.2015.00051
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for microtubules in angiosperm pollen tube growth highlight new research cues

Abstract: In plants, actin filaments have an important role in organelle movement and cytoplasmic streaming. Otherwise microtubules (MTs) have a role in restricting organelles to specific areas of the cell and in maintaining organelle morphology. In somatic plant cells, MTs also participate in cell division and morphogenesis, allowing cells to take their definitive shape in order to perform specific functions. In the latter case, MTs influence assembly of the cell wall, controlling the delivery of enzymes involved in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 222 publications
(342 reference statements)
0
17
0
Order By: Relevance
“…During pollen tube growth, the establishment of a narrow growth site at the plasma membrane of growing tip requiring continuous targeting of Golgi-derived vesicles to this site and their fusion with the plasma membrane is essential for proper polarized cell growth (Emons and Ketelaar 2009;Zársky et al 2009;Onelli et al 2015). Highly active vesicle trafficking processes also occur in microspores and tapetal cells during pollen development (Scott et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…During pollen tube growth, the establishment of a narrow growth site at the plasma membrane of growing tip requiring continuous targeting of Golgi-derived vesicles to this site and their fusion with the plasma membrane is essential for proper polarized cell growth (Emons and Ketelaar 2009;Zársky et al 2009;Onelli et al 2015). Highly active vesicle trafficking processes also occur in microspores and tapetal cells during pollen development (Scott et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…In pollen tubes, MTs control movement of the male germ unit [ 21 ] and positioning of large vacuoles in the distal regions of the tube [ 22 ]. More recently, it was reported that MTs also play a role in exocytosis in the central region of the tip and in endosome trafficking [ 7 , 19 ]. Specifically, MT perturbation by nocodazole delayed transport of endocytic vesicles to the vacuoles [ 7 ] and redirected the endocytosed material to the Golgi apparatus, suggesting that MTs are involved in transport of endosomes towards vacuoles [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another plant structure characterized by polarized fast growth is the pollen tube. MTs play a role in secretion and endocytosis, acting as tracks for vesicular transport and deposition of proteins/lipids at the tip membrane [ 27 ]. Interestingly, overexpression of a Picea wilsonii pollen-specific alpha tubulin gene increases pollen tube growth rate in Arabidopsis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%